The Development of Multicultural Counseling Model Based on Tudang Sipulung Culture to Improve the Social Skills of Indonesian Students - Bakhtiar, Muhammad Ilham; Saman, Abdul; AR, Nur Halim (Universitas Negeri Makassar, 2023)
The purposes of this study are: (1) To develop a multicultural counseling model integrating cultural values of tudang sipulung to improve the social skills of students at Junior High School 2 Minasatene; (2) the investigate if the multicultural counseling model through the integration of tudang sipulung values is effective to improve the social skills of students at Junior High School 2 Minasatene. The method employed in this study was the Research and development (R & D). We initiated the study with need analysis and continued with the development of the product or model, model validation, test on the model to a small group, and revision. The targeted output was a product in the form of a Guide of Multicultural Counseling Model published in an accredited national journal with accepted status. Results of this study are: (1) Based on the evaluation from the experts, the guide of multicultural counseling model based on tudang sipulung values is feasible to use and distributed to teachers and students at school according to indicators, purposes, feasibility, and accuracy. (2) After performing tests on small groups consisting of 10 students to measure the effectiveness of the implementation of this model, we found Asymp.Sig. (2-tailed) =.004. Because it was smaller than 0,05, it could be concluded that the Ha was accepted, meaning there was a difference before and after the implementation of multicultural counseling that was developed, and it was regarded to be very feasible to be implemented and effective to improve students’ social skills.